Polypeptide Composition of Urea- and Heat-Resistant Mutants of Poliovirus Types 1 and 2 - Fennell, Robert (1974)
Five urea-resistant and two heat-resistant mutants of poliovirus types 1 and 2 were isolated and their structural and nonstructural polypeptides compared to those of their wild-type, parental strains in an attempt to correlate mutant phenotypes with alterations in specific capsid polypeptides. Four of the seven mutants were found to contain polypeptides which differed in molecular weight from their respective parental viruses. However, resistance of virions to heat- or urea-inactivation could not be attributed to changes in particular capsid polypeptides because alterations were detected in all but one of the capsid components. For two of the urea-resistant mutants and one heat-resistant mutant, no differences were found in the molecular weights of the capsid and noncapsid polypeptides. These results, and the fact that at least 12 selective treatments were required to obtain stable mutants, indicate that: (i) such phenotypes probably can be expressed by mutations affecting one or more of the larger capsid polypeptides, and (ii) such phenotypes reflect multiple mutational steps.